2015
DOI: 10.1007/s00343-016-5350-4
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lipid and gross energy affect protein utilization in the rare minnow Gobiocypris rarus

Abstract: A bstractAn 8-week feeding trial was conducted to detect the optimal dietary protein and energy, as well as the eff ects of protein to energy ratio on growth, for the rare minnow ( Gobiocypris rarus ), which are critical to nutrition standardization for model fi sh. Twenty-four diets were formulated to contain three gross energy (10, 12.5, 15 kJ/g), four protein (20%, 25%, 30%, 35%), and two lipid levels (3%, 6%). The results showed that optimal dietary E/P was 41.7-50 kJ/g for maximum growth in juvenile rare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…If an animal’s growth is significantly affected by adverse conditions, then its welfare could deteriorate significantly [ 40 ]. Previous studies have shown that the factors affecting the growth of rare minnows include nutrients [ 41 , 42 ], water temperature [ 43 ] and other physical and chemical characteristics of their water environment, feeding, and other culturing strategies [ 43 , 44 , 45 ]. Therefore, these impact factors are restricted or controlled in the standard drafts of rare minnows to ensure their basic welfare.…”
Section: Discussionmentioning
confidence: 99%
“…If an animal’s growth is significantly affected by adverse conditions, then its welfare could deteriorate significantly [ 40 ]. Previous studies have shown that the factors affecting the growth of rare minnows include nutrients [ 41 , 42 ], water temperature [ 43 ] and other physical and chemical characteristics of their water environment, feeding, and other culturing strategies [ 43 , 44 , 45 ]. Therefore, these impact factors are restricted or controlled in the standard drafts of rare minnows to ensure their basic welfare.…”
Section: Discussionmentioning
confidence: 99%